Exploring the perceptions of caregivers regarding their homework involvement with institutionalised children : an application of three leve-one constructs of the Hoover-Dempsey and Sandler Model (1995). - McQuade, Val-Lyn (My University, 2011)
The increased number of orphaned and vulnerable children (OVC) in South Africa is thought to be serious. The dramatic increase in OVC as a result of factors such as neglect, poverty, abuse and disease places emphasis on the care which such children receive. Due to the fact that many families cannot take on the burden of an extra child, such children find shelter on the streets or are placed in institutions. Seminal research has documented the negative effects that institutionalisation has on children especially in relation to their cognitive development. At the heart of institutionalised children’s development are the caregivers which attend to the children’s needs, such as homework. It is thought that homework is essential to educational achievement as well as cognitive development and requires the input of a parent or caregiver. Due to the fact that the IQ of children within institutions is thought to be lower than that of their peers in a home environment, the type of homework mediation instutionalised children receive is important. In order to gain insight into the homework involvement process within the institution, this research sought to investigate the perceptions of caregivers regarding their homework involvement with instutionalised children through the application of three level-one constructs of the Hoover-Dempsey and Sandler model (1995). The Hoover-Dempsey and Sandler model (1995) is concerned with explaining the factors which influence or affect parents’ decisions to become involved in their children’s education. The primary aim of this research was to investigate the perceptions of caregivers regarding their homework involvement with institutionalised children, applying the three level-one constructs of the Hoover-Dempsey and Sandler model (1995). This research was of a qualitative exploratory nature, and placed emphasis on the in-depth insight of caregivers. Data was collected through a self-developed semi-structured interview schedule and data analysis employed a thematic content analysis whereby themes and sub-themes were identified and discussed under the three level-one constructs of the Hoover-Dempsey and Sandler model (1995).